(untitled) (Academicia Globe: Inderscience Research, 2022)
Literature data of native researchers about influence of adsorbent pore structure and pore dimensions on kinetics, activ ation energy and limiting stage nature are generalized. Data of native and foreign researchers about adsorption of a number of heavy metal cations (Ni(II), Co(II), Zn(II), Cu(II), Cd(II)), mixtures containing Cu(II), Zn(II) and anions (F–, Cr(VI)) on nature clay adsorbents are considered and generalized. Possibility of essential increase of specific adsorption of nature sorbents by their surface modification is shown.